2020
DOI: 10.4103/ijpvm.ijpvm_552_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of weekly iron–Folic acid supplementation with and without health education on anemia in adolescent girls: A comparative study

Abstract: Background: Iron deficiency is the most common and widespread nutritional disorder in the world, affecting a large number of children and women in developing countries and constituting a public health condition of epidemic proportions. Weekly iron and folic acid supplementation (WIFS) with health education has been demonstrated to be effective in reducing anemia in adolescent school going girls. We assessed the impact of WIFS with and without health education on anemia in adolescent school girls o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Therefore, iron supplementation and avoiding smoke exposure are acceptable strategies for combating adolescent anemia. This finding is consistent with another study in Delhi that stated the school-based Fe intervention is a multi-sector collaboration platform that has the potential to provide leverage for stunting prevention in adolescents (Singh et al, 2020).…”
Section: Preventionsupporting
confidence: 91%
“…Therefore, iron supplementation and avoiding smoke exposure are acceptable strategies for combating adolescent anemia. This finding is consistent with another study in Delhi that stated the school-based Fe intervention is a multi-sector collaboration platform that has the potential to provide leverage for stunting prevention in adolescents (Singh et al, 2020).…”
Section: Preventionsupporting
confidence: 91%
“…Educational games are effective in changing behaviour related to nutrition in adolescents[33]. Providing education about nutrition in schools and iron supplementation interventions every week is effective in increasing adherence to Fe tablet consumption, reducing side effects, and treating anaemia in female adolescents at school[34]. The previous study showed a significant effect between weekly iron supplementation in schools with haemoglobin levels and reducing the incidence of anaemia in female adolescents.The level of adherence of female adolescents in taking iron supplement tablets is one of the effective factors in increasing iron supplementation[35].Giving health education about anaemia and nutrition effectively increased female adolescents' knowledge.…”
mentioning
confidence: 99%